Neurocognitive, psychiatric, and substance use characteristics in opioid dependent adults. (September 2016) - Arias, Franchesca; Arnsten, Julia H.; Cunningham, Chinazo O.; Coulehan, Kelly; Batchelder, Abigail; Brisbane, Mia; Segal, Katie; Rivera-Mindt, Monica
Abstract: Aims: To describe neurocognitive function among opioid-dependent adults seeking buprenorphine treatment and to explore the impact of lifetime psychiatric conditions on neurocognitive function. To explore the additive interaction of patient-based characteristics that may help to inform treatment. Design: Cross-sectional assessment of neurocognitive function, substance use, and psychiatric characteristics of adults seeking buprenorphine treatment within substance use treatment centers in New York City. Participants: Thirty-eight opioid-dependent adults seeking buprenorphine treatment. Measurements: A comprehensive battery, which included measures of executive functioning, learning, memory, verbal fluency, attention, processing speed, and motor functioning were administered. The Wide Range Achievement Test-Third Edition, the Composite International Diagnostic Interview, and an audio computer assisted structured interview were also completed. Correlations and independent sample t -tests were used to ascertain group differences. Findings: Thirty-nine percent of participants were impaired in global neurocognitive function ( n  = 15). Over one third were impaired in either: learning ( n  = 28), memory ( n  = 26), executive functioning ( n  = 17), motor functioning ( n  = 17), attention/working memory ( n  = 14) or verbal fluency ( n  = 12). Lifetime history of alcohol dependence was associated with impairment in global neurocognitive, executive functioning, and motor functioning. Lifetime history of cocaine dependence was associated with impairment in executive functioning and motor functioning (all p 's < 0.05). Major depressive disorder history was not associated with neurocognitive impairment. Conclusions: Among this sample of opioid-dependent adults, there were high rates of global and domain-specific neurocognitive impairment, with severe impairment in learning and memory. Lifetime alcohol and cocaine dependence were associated with greater neurocognitive impairment, particularly in executive functioning. Because executive functioning is critical for decision-making and learning/memory dysfunction may interfere with information encoding, these findings suggest that opioid-dependent adults may require enhanced support for medical decision-making. Highlights: Community-dwelling adults, of diverse socio-economic status, seeking buprenorphine treatment. A comprehensive neurocognitive battery that evaluated baseline cognitive functioning. Psychiatric, functional, and psychological factors were examined. Interpreted overall performance emphasizing the effect of multiple factors on neurocognitive performance. Adults who present for opioid agonist treatment with buprenorphine, may exhibit diminished neurocognitive functioning. Also, preexisting alcohol and cocaine use disorders are associated with poorer scores.